2015
DOI: 10.4103/0970-4388.160394
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral response and pain perception to computer controlled local anesthetic delivery system and cartridge syringe

Abstract: Usage of techniques which enhance behavioral response in children like injections with CCLAD can be considered as a possible step toward achieving a pain-free pediatric dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…15 The available literature shows that the majority of previous studies conducted to compare the computer-controlled injection systems with conventional syringes for pain during injection showed results in favor of computer-controlled injection systems. 2,16,17 These results were contradicted in a study by Goodell et al, 19 where the conventional atraumatic syringe injection technique was found to be superior to a controlled injection pressure system in pain perception and procedure tolerance and in reducing post-injection dental anxiety. 18 The present study did not show any difference between the computercontrolled and self-aspirating syringe in the pain during injection.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…15 The available literature shows that the majority of previous studies conducted to compare the computer-controlled injection systems with conventional syringes for pain during injection showed results in favor of computer-controlled injection systems. 2,16,17 These results were contradicted in a study by Goodell et al, 19 where the conventional atraumatic syringe injection technique was found to be superior to a controlled injection pressure system in pain perception and procedure tolerance and in reducing post-injection dental anxiety. 18 The present study did not show any difference between the computercontrolled and self-aspirating syringe in the pain during injection.…”
Section: Discussionmentioning
confidence: 94%
“…The possible reason stated was the injection pressure with cartridge syringe, which is difficult to control. 16,17 Saloum et al 19 reported that injection with self-aspirating syringe was more painful than injection with computer-controlled devices. 19 The operator technique and tactile skill in syringe injections and site of injection (right or left) were the possible reasons for differences in pain perception in the study by Saloum et al Pain differed significantly between the conventional and CCLADS and between the conventional and selfaspirating syringe 24 hours after injection.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the released researches support the efficacy of using these delivery systems in reducing the pain of local anesthesia injection. [ 43 44 45 46 ]…”
Section: Resultsmentioning
confidence: 99%
“…The flow of injection is adjusted to, among others, tissue resistance so the patient does not feel the expansion of anesthetic solution. Both children and adult patients can benefit from the advantages of these devices [ 8 , 13 ]. Since the introduction of computer-controlled local anesthetic delivery systems, studies have compared its effectiveness to traditional methods of local anesthesia.…”
Section: Discussionmentioning
confidence: 99%